Holistic production analysis for actuator manufacturing using data mining - Sand, Christian; Bogus, Kim; Kunz, Sabrina; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
Holistic production optimizations within large-scale productions are not yet used because classic methods like Six Sigma or DoE are less expedient when it comes to huge or more complex data sets. Thus no standardized analysis for integrated production optimization exists, to realize 0 ppm defects. This paper introduces a holistic analytics approach using data mining techniques to reduce the error and scrap rate, addressing experts and non-specialized workers.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Actuator; Data Mining; Optimization; Tool Wear